Free tensor fascia lata true‐perforator flap transfer for reconstruction of the calcaneal soft tissue defect complicated with osteomyelitis in a patient with alcohol‐induced Charcot foot: A case report and literature review. Issue 5 (17th February 2021) - Tsuihiji, Kanako; Daniel, Bassem W.; Kageyama, Takashi; Sakai, Hayahito; Fuse, Yuma; Tsukuura, Reiko; Yamamoto, Takumi
Abstract: Charcot foot is can result in bone deformities and soft tissue defects. We report a case of alcohol‐induced Charcot (AIC) foot with soft tissue defect including the weight‐bearing zone of the heel and osteomyelitis, which was successfully reconstructed with free tensor fascia lata true‐perforator flap (TFLtp). A 56‐year‐old male suffered from AIC foot with an 18 × 6 cm defect. Based on the preoperative ultrasound, we identified the overlying upper thigh area offering one of the thickest dermis. A TFLtp flap was raised sparing the TFL muscle based on one perforator without including the main trunk of the transverse/ascending branch of the lateral femoral circumflex vessel. The TFLtp flap was transferred to the heel and anastomosed to the posterior tibial artery in an end‐to‐side fashion. The patient complained no postoperative discomfort of the donor site and was able to walk on his foot after 5 weeks. This case report highlights that the TFLtp flap may offer thick dermis, faster surgery due to perforator level dissection and a concealed donor site.